2015
DOI: 10.1177/0731121415586635
|View full text |Cite
|
Sign up to set email alerts
|

Social Class, Family Formation, and Delinquency in Early Adulthood

Abstract: Recent research suggests increasing heterogeneity in the transition from adolescence to early adulthood. This study considers how this heterogeneity may influence delinquency between these two developmental periods. We focus on the role of family transitions, educational attainment, and employment in predicting risk of nonviolent delinquency and substance use, as well as disparities in transitions across socioeconomic status subgroups. Data are from the National Longitudinal Study of Adolescent to Adult Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 62 publications
(93 reference statements)
1
17
0
Order By: Relevance
“…"Low parental involvement, weak family cohesion, and poor parent-child communication increase risk for delinquency." This emphasizes and agrees with Kuhl et al (2016) that a weak familial structure, such as a disconnect between a parent and child, can lead to delinquent behavior in adolescence and potentially carry over to high-risk behavior in adulthood. Booth, Farrell and Varano (2008: 440) explain delinquency can transition from youth to adulthood.…”
Section: Familial Formation and Transition From Adolescence Into Earlsupporting
confidence: 70%
See 4 more Smart Citations
“…"Low parental involvement, weak family cohesion, and poor parent-child communication increase risk for delinquency." This emphasizes and agrees with Kuhl et al (2016) that a weak familial structure, such as a disconnect between a parent and child, can lead to delinquent behavior in adolescence and potentially carry over to high-risk behavior in adulthood. Booth, Farrell and Varano (2008: 440) explain delinquency can transition from youth to adulthood.…”
Section: Familial Formation and Transition From Adolescence Into Earlsupporting
confidence: 70%
“…Booth, Farrell and Varano (2008: 440) explain delinquency can transition from youth to adulthood. In contrast to Kuhl et al (2016) and Aiyer et al (2013), their study found: "parental attachment was not a significant predictor of risky behavior." Despite the fact that this study found an insignificant relationship, you can see that findings can vary based on samples.…”
Section: Familial Formation and Transition From Adolescence Into Earlmentioning
confidence: 94%
See 3 more Smart Citations